HUBUNGAN LAMA PUASA DAN KADAR GLUKOSA DARAH DENGAN KEJADIAN POST ANESTHETIC SHIVERING (PAS) PADA PASIEN PASCASPINAL ANESTESI DI RSUD PANDAN ARANG BOYOLALI - Lira Despiana Gracia; Ganik Sakitri; Halima Aulia Ita Maghfiroh (STKIP Subang, 2026)
Introduction : Post-anesthetic shivering (PAS) is a common complication after spinal anesthesia and can cause discomfort and increased metabolic demands. One factor suspected of contributing to PAS is excessive preoperative fasting and changes in blood glucose levels due to fasting. Preoperative fasting practices that do not comply with recommendations are still common, therefore, this study was conducted to analyze the relationship between fasting duration and blood glucose levels with the incidence of post-anesthetic shivering in post-spinal anesthesia patients at Pandan Arang Boyolali Hospital. Methods : This was a quantitative study with an observational analytical design using a cross-sectional approach. The study population was all patients undergoing surgery with spinal anesthesia, with a sample of 30 respondents selected using consecutive sampling technique. Independent variables included fasting duration and fasting blood glucose levels, while the dependent variable was the incidence of Post Anesthetic Shivering. Data were collected through interviews and medical records for fasting duration, blood glucose measurements using a glucometer, and shivering observations using the Bedside Shivering Assessment Scale (BSAS). Data analysis was performed using the Spearman Rank correlation test. Results : The results showed that most respondents fasted for 9–11 hours (70.0%) with fasting blood glucose levels of 83–99 mg/dL (80.0%). The incidence of PAS was most commonly found in grade 2 (36.7%) and grade 3 (30.0%). There was a significant and strong relationship between fasting duration and the incidence of PAS (p = 0.000; r = 0.861), as well as a significant relationship between blood glucose levels and the incidence of PAS (p < 0.05). Recommendation : This study recommends optimizing preoperative fasting management and blood glucose monitoring to prevent post-anesthetic shivering in patients undergoing spinal anesthesia.